2019
DOI: 10.32845/bsnau.2019.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Universities as a driving force for circular economy implementation in China

Abstract: The successful implementation of circular economy (CE) model needs the understanding and support of the whole public on the CE concept and knowledge, and then turns it into CE practice in the daily life. Colleges and universities are one of the direct driving forces in the implementation of CE model. Universities circular economy education (UCEE) is a novel concept, which refers to a kind of lifelong education with exerting the all the educational assets and influence of colleges and universities to radiate ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…It was agreed that the SAUoT serves as the living laboratory for operationalizing the deployment of different 4IR technologies toward achieving this purpose. This concurs with postulations raised in similar literature as it concerns the nexus between digital technologies and circular economy implementation (Hoosain et al, 2020;Liu et al, 2021), the role of HEIs in driving sustainability performance in regional and national contexts through transfer of appropriate technologies and expertise (Soares et al, 2020;Thomas and Pugh, 2020;Garcia-Alvarez-Coque et al, 2021), and improved CE implementation performance across multiple scales between HEIs and regional and economic sectoral contexts (De Medici et al, 2018;Qu and Shevchenko, 2019;Qu et al, 2020;Rokicki et al, 2020;Stephan et al, 2020).…”
Section: Presentation and Discussion Of Findingssupporting
confidence: 84%
“…It was agreed that the SAUoT serves as the living laboratory for operationalizing the deployment of different 4IR technologies toward achieving this purpose. This concurs with postulations raised in similar literature as it concerns the nexus between digital technologies and circular economy implementation (Hoosain et al, 2020;Liu et al, 2021), the role of HEIs in driving sustainability performance in regional and national contexts through transfer of appropriate technologies and expertise (Soares et al, 2020;Thomas and Pugh, 2020;Garcia-Alvarez-Coque et al, 2021), and improved CE implementation performance across multiple scales between HEIs and regional and economic sectoral contexts (De Medici et al, 2018;Qu and Shevchenko, 2019;Qu et al, 2020;Rokicki et al, 2020;Stephan et al, 2020).…”
Section: Presentation and Discussion Of Findingssupporting
confidence: 84%
“…Waste sorting plans within the waste management system in societies require accurate planning and cooperation of all residents. In particular, successful waste management programs for colleges and universities, as a large community, need the support and effective participation of residents [10]. College students are the most important part of college community residents, and their attitude and participation in campus waste separation practices play a key role in the successful implementation of college waste management projects [11].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the use of a novel proposed framework, namely the 'Backcasting and Eco-design for Circular Economy (BECE)' framework, as a novel combination is useful for facilitating CE solutions in the HEIs. Still, in the HEI context, Qu, D & Shevchenko, T (2019) analyzed recent research related to the roles of HEIs for CE implementation in China. From their review, they confirmed that university students play important roles in the CE education process.…”
Section: Literature Reviewmentioning
confidence: 99%